Potential of an Electronic Health Record-Integrated Patient Portal for Improving Care Plan Concordance during Acute Care - Dalal, Anuj K.; Dykes, Patricia; Samal, Lipika; McNally, Kelly; Mlaver, Eli; Yoon, Cathy S.; Lipsitz, Stuart R.; Bates, David W. (Applied Clinical Informatics, 2019)
Background Care plan concordance among patients and clinicians during hospitalization is suboptimal.Objective This article determines whether an electronic health record (EHR)-integrated patient portal was associated with increased understanding of the care plan, including the key recovery goal, among patients and clinicians in acute care setting.Methods The intervention included (1) a patient portal configured to solicit a single patient-designated recovery goal and display the care plan from the EHR for participating patients; and (2) an electronic care plan for all unit-based nurses that displays patient-inputted information, accessible to all clinicians via the EHR. Patients admitted to an oncology unit, including their nurses and physicians, were enrolled before and after implementation. Main outcomes included mean concordance scores for the overall care plan and individual care plan elements.Results Of 457 and 283 eligible patients approached during pre- and postintervention periods, 55 and 46 participated in interviews, respectively, including their clinicians. Of 46 postintervention patients, 27 (58.7%) enrolled in the patient portal. The intention-to-treat analysis demonstrated a nonsignificant increase in the mean concordance score for the overall care plan (62.0–67.1, adjusted p = 0.13), and significant increases in mean concordance scores for the recovery goal (30.3–57.7, adjusted p < 0.01) and main reason for hospitalization (58.6–79.2, adjusted p < 0.01). The on-treatment analysis of patient portal enrollees demonstrated significant increases in mean concordance scores for the overall care plan (61.9–70.0, adjusted p < 0.01), the recovery goal (30.4–66.8, adjusted p < 0.01), and main reason for hospitalization (58.3–81.7, adjusted p < 0.01), comparable to the intention-to-treat analysis.Conclusion Implementation of an EHR-integrated patient portal was associated with increased concordance for key care plan components. Future efforts should be directed at improving concordance for other care plan components and conducting larger, randomized studies to evaluate the impact on key outcomes during transitions of care.Clinical Trials Identifier NCT02258594.
Keywords: patient engagement; patient portals; care plan concordance; patient–clinician communication